The Effect of Basil Leaf (Ocimum basilicum) Decoction on Vaginal Discharge Among Women of Reproductive Age (WRA) at TPMB Midwife L, Cikampek, 2026 - Liana Bintang Permata; Dita Humaeroh; Maulida Lathifah (Public Health Journal, 2026)
Vaginal discharge is one of the reproductive health problems frequently experienced by women of reproductive age (WRA), particularly when accompanied by changes in color, odor, itching, or other complaints. Basil leaves (Ocimum basilicum) contain bioactive compounds such as flavonoids, saponins, tannins, eugenol, and essential oils, which have been associated in previous studies with antibacterial, antifungal, and anti-inflammatory activities. This study aimed to determine the effect of basil leaf decoction on vaginal discharge among WRA at TPMB Midwife L, Cikampek, in 2026. The study used a quantitative approach with a quasi-experimental one-group pretest-posttest design. The population consisted of 32 WRA experiencing vaginal discharge, and 30 respondents were selected using purposive sampling. The intervention consisted of 10 grams of basil leaves boiled in 500 mL of water and applied externally to the outer genitalia/vulva twice daily, in the morning and afternoon, for seven days. Measurements were conducted using a questionnaire/observation sheet before and after the intervention. Data were analyzed using the Shapiro-Wilk test and Wilcoxon Signed Rank Test. The mean vaginal discharge score decreased from 1.57 (SD 0.504) to 1.23 (SD 0.430). The Wilcoxon test produced p=0.000 (